2004
DOI: 10.1128/jvi.78.12.6171-6179.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Reovirus by Mycophenolic Acid Is Associated with the M1 Genome Segment

Abstract: Mycophenolic acid (MPA), an inhibitor of IMP dehydrogenase, inhibits reovirus replication and viral RNA and protein production. In mouse L929 cells, antiviral effects were greatest at 30 g of MPA/ml. At this dosage, MPA inhibited replication of reovirus strain T3D more than 1,000-fold and inhibited replication of reovirus strain T1L nearly 100-fold, compared to non-drug-treated controls. Genetic reassortant analysis indicated the primary determinant of strain-specific differences in sensitivity to MPA mapped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
(75 reference statements)
2
18
0
Order By: Relevance
“…Mycophenolic acid is an orally available immunosuppressant used for prevention of posttransplant organ rejection. Mycophenolic acid has activity against many RNA and DNA viruses (4,9,16,22,23,29,35,43), including poxviruses (9,19,49). Its antiviral activity is linked to inhibition of purine metabolism, insofar as virus replication is rescued by exogenous guanosine.…”
Section: Resultsmentioning
confidence: 99%
“…Mycophenolic acid is an orally available immunosuppressant used for prevention of posttransplant organ rejection. Mycophenolic acid has activity against many RNA and DNA viruses (4,9,16,22,23,29,35,43), including poxviruses (9,19,49). Its antiviral activity is linked to inhibition of purine metabolism, insofar as virus replication is rescued by exogenous guanosine.…”
Section: Resultsmentioning
confidence: 99%
“…Gallate derivatives that display antiviral effects are used as antioxidant food additives, including EÀ310 (propyl gallate), EÀ311 (octyl gallate), and EÀ312 (lauryl gallate) (39). Mycophenolic acid has additionally been identified as an anti-reoviral agent, acting as a reversible inhibitor of eukaryotic IMP dehydrogenase (IMPDH) (40). Another study demonstrated that chestnut and quebracho wood extracts containing tannin show antiviral activity against avian reovirus and metapneumovirus (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, in normal cells, viral infection triggers PKR phosphorylation, which in turn leads to inhibition of viral gene translation, cell apoptosis and termination of viral infection. Apart from the natural mechanism present in non-neoplastic cells, reovirus infection can be contained by mycophenolic acid, an immunosuppressive agent [28]. The major disadvantage of this oncolytic vector is its nonalterable ten segments of genome, which renders this virus impossible to engineer for specific mutations [29].…”
Section: History Of Oncolytic Virotherapymentioning
confidence: 99%